The New Family Arrangements to Overcome Traditionalism: Pluralism and the Concretisation of Fundamental Rights in Brazil - Maliska, Marcos Augusto; de Jesus, Marilaine Moreira (As-Siyasi: Journal of Constitutional Law, 2023)
Traditionalism is an ideology that advocates for a government founded on principles surpassing mere human and individual aspects. In traditional symbolism, the supernatural principle is regarded as masculine and feminine. Traditionalism underscores the necessity for the family entity to acknowledge the metaphysical dyad distinguishing the masculine from the feminine, contending that the sole legitimate family form is constituted by the union of a man and a woman and their offspring. This paper examines the shift from traditionalism to constitutional pluralism within family entities. It aims to comprehend how constitutional pluralism acknowledges the diversity of family forms and facilitates societal changes in the concept of the family while circumventing state censorship and bolstering individual liberty. The approach utilized is one of normative juridical inquiry. The study reveals that new family structures, rooted in constitutional pluralism, foster the displacement of traditionalism, thereby establishing a new paradigm for interpreting the concept of the family as defined by the Constitution. Traditionalism, having historically occupied a dominant stance regarding the family, yields to pluralism. Realizing fundamental rights ensures the diversity of family entities, including the traditional family's rightful claim to existence. Viewed from the vantage point of a pluralistic family constitutional framework, traditionalism should not be perceived as antagonistic to pluralism but rather as one of its valid manifestations, a legitimate approach to experiencing life and perceiving the world